Leukocyte Profile Analysis in Cats with Otitis Caused by Otodectes cynotis Infestation Following Ivermectin Treatment - Rahmawati, Kadek; Hannifa, Bentary; Tita, Yessa; Yunita, Rizky; Lyonis, Arszheta; Krisna, Ibrahim; Khairani, Balqis (Universitas Airlangga, 2025)
Otitis in domestic cats is an inflammation of the ear caused by bacterial, fungal, or parasitic infections, especially ear mites (Otodectes cynotis). It is common in cats and can cause itching, discomfort, and more severe secondary infections if left untreated. Ivermectin is an antiparasitic agent that is effective in controlling various parasitic infections, including ear mites in cats. The mechanism of action of ivermectin is by inhibiting the nerve activity of the parasite, causing paralysis and death of the parasite. This study aimed to evaluate the effectiveness of ivermectin therapy on leukocyte profile in cats with otitis due to ear mite Otodectes cynotis parasite infestation. This study used a Pretest-Posttest Control Group Design involving two groups of domestic cats: a treatment group (K+) receiving ivermectin therapy and a control group (K-) receiving no treatment. Leukocyte profiles were analyzed using a hematology analyzer. The results showed that ivermectin was effective in reducing the total leukocyte count. A decrease in the number of leukocytes, especially eosinophils and neutrophils, indicates an improvement in the inflammation and healing stage of the cat's body. Thus, ivermectin was shown to be effective in suppressing Otodectes cynotis parasite invasion and improving the immunological status of domestic cats through its effect on leukocyte profile.